The Impact Of Different Lateral Size Of Graphene Oxide On The Performance Of The Emulsified Acrylate-Based Pour Point Depressant And Its Application In Crude Oil - Darryl Wong, Jun Chen (Universiti Sains Malaysia, 2018)
The different lateral size of GOs were obtained through ultrasonication method at 0 min, 10 min, 30 min, 60 min and 100 min. The SEM results shows that the longer the ultrasonication time, the smaller the average lateral size of the GO nanosheets. The results from FTIR is used to shows the presence of the oxygen functional group in the GO nanosheets after subjected to ultrasonication. The addition of different lateral size GO into the emulsified acrylate-based PPD-GO shows that the acrylate-based droplets size increases, more polydisperse and reduce in zeta potential. However, when the emulsified acrylate PPD-GO is at isothermal and freeze thaw condition, the effect of the different lateral size of the GO after aging not that significant. The rheological measurement shows that 10 min is the optimum ultrasonication time to produce the ideal lateral size of GO nanosheets that leads to improvement in flowabiltiy and stability of the emulsified acrylate-based PPD-GO. Besides, it shows the highest reduction of pour point on the crude oil and improve rheological behaviour of the crude oil in terms of shear stress and viscosity. Exceeding the optimum ultrasonication time, the reducing lateral size of GO will produce negative impact on the flowability and the stability of the emusified acrylate PPD-GO and its performance in crude oil. Lastly, the study on Herschel-Buckley model has proven to be more accurate in prediction of yield stress and fluid behaviour of emulsified acrylate-based PPD-GO compare to crude oil.